High levels of total ammonia nitrogen as NH4+ are stressful and harmful to the growth of Nile tilapia juveniles - doi: 10.4025/actascibiolsci.v35i4.17291 (Acta Scientiarum. Biological Sciences, 2013)
This study determined whether high levels of total ammonia nitrogen (TAN) as NH4+ are harmful to the growth performance of Nile tilapia juveniles. Fingerlings (0.31 ± 0.04 g) were assigned to 30 polyethylene 100-L tanks in a roofed room for 12 rearing weeks. There were increasing levels of TAN by increased NH4Cl application rates (0.0; 0.25 and 0.50 g tank-1 week-1) at three conditions of water pH (acidic, 6.2 ± 0.5; neutral, 7.2 ± 0.8 and alkaline, 8.8 ± 0.3). The application of HCl to acidic tanks caused 100% of TAN to be converted into NH4+. The poorest growth performance results were observed for the alkaline tanks subjected to the highest application of NH4Cl. In acidic tanks, fish survival has dropped in those tanks under the highest application rate of NH4Cl. Tilapia growth was lower in neutral tanks when the NH4Cl application rate increased to 0.50 g tank-1 week-1. It was concluded that waterborne ionized ammonia (NH4+) is indirectly toxic to tilapia due to the harmful metabolites derived from it, such as nitrite and chloramines as well as due to water acidification.